Effect of substrate temperature on the properties of RF sputtered CdS thin films for solar cell applications - Das N.K.; Chakrabartty J.; Farhad S.F.U.; Sen Gupta A.K.; Ikball Ahamed E.M.K.; Rahman K.S.; Wafi A.; Alkahtani A.A.; Matin M.A.; Amin N. (Elsevier B.V., 2023)
We report the effect of substrate temperature (25300 C) on the structural, optical and electrical properties of Cadmium Sulphide (CdS) thin films deposited onto glass substrate by Radio Frequency (RF) magnetron sputtering. The structural, morphological, optical and electrical properties of the films were characterized by X-ray diffraction (XRD), Field emission scanning electron microscopy (FE-SEM), UVVIS-NIR spectroscopy and Hall Effect measurement respectively. The XRD studies showed that the films were polycrystalline with hexagonal wurtzite structure preferentially oriented along the (0 0 2) plane parallel to the substrate surface. The XRD data analysis further revealed the crystallite size of the nanocrystalline films i.e. 2224 nm exhibiting the fact that crystallite size increased with increasing the substrate temperature. The FE-SEM images along with energy dispersive spectroscopy (EDS) studies confirmed the homogeneous, compact and pin-hole free surface morphology. The UVVIS-NIR studies unveiled the optical transmittance in the range of 7590% after 540 nm of the wavelength of light. The optical band gaps were found to be decreasing from 2.34 eV to 2.26 eV with increasing the substrate temperature. The films were characterized as n-type as evidenced by the Hall Effect measurement. The carrier mobility was found to be increasing gradually from 5.53 to 12.57 cm2/Vs by increasing the substrate temperature from room temperature to 300 C due to the improvement of crystalline quality and grain size of the films. The results showed good optical and electrical properties of the films deposited at 300 C which are suitable to use as window layer in thin film based solar cells. 2020 The Authors